2022
DOI: 10.1007/s00392-021-01957-1
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran versus vitamin K antagonists for atrial fibrillation in clinical practice: final outcomes from Phase III of the GLORIA-AF registry

Abstract: Background Prospectively collected, routine clinical practice-based data on antithrombotic therapy in non-valvular atrial fibrillation (AF) patients are important for assessing real-world comparative outcomes. The objective was to compare the safety and effectiveness of dabigatran versus vitamin K antagonists (VKAs) in patients with newly diagnosed AF. Methods and results GLORIA-AF is a large, prospective, global registry program. Consecutive patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 18 publications
1
27
0
1
Order By: Relevance
“…The primary papers from GLORIA-AF Phase III registry comparing the different anticoagulation strategies have recently been published. 21 , 22 …”
Section: Methodsmentioning
confidence: 99%
“…The primary papers from GLORIA-AF Phase III registry comparing the different anticoagulation strategies have recently been published. 21 , 22 …”
Section: Methodsmentioning
confidence: 99%
“…Complete details on the design of the GLORIA-AF study have been previously reported, 20,21 as well as the primary papers comparing dabigatran versus VKA and other NOACs. 22,23 Briefly, patients with new-onset nonvalvular AF and CHA 2 DS 2 -VASc score !1 were consecutively enrolled between 2011 and 2016 (2011-2014 for phase II, and 2014-2016 for phase III). Patients enrolled in phase II who initiated dabigatran were prospectively followed up for 2 years, while all patients enrolled in phase III (irrespective of the antithrombotic treatment) were followed up for 3 years.…”
Section: Methodsmentioning
confidence: 99%
“…Details on follow-up and outcomes for phase II and phase III were reported elsewhere. 23,25 During follow-up, data regarding treatment discontinuation and major adverse outcomes were collected, until study withdrawal, death, or end of study. Nonpersistence was defined as either discontinuation or study termination.…”
Section: Follow-up Persistence and Major Adverse Outcomesmentioning
confidence: 99%
See 2 more Smart Citations